Dangerous goods export procedures (International Seven Journal of Multidisciplinary, 2023)
This work aims to understand the process of exporting dangerouscargo, which tends to be somewhat cautious, as it is necessary tofollow rules and regulations, which are essential in this operation. The risk content of these segments is characterized as explosives, flammable liquids, oxidants, poisonous, corrosive and pollutants, as defined by law 10.233/01. One of the main entities that regulate theexport procedure is the IMDG (International Maritime DangerousGoods). That has all the means for conservation, packaging, labeling, documentation, last and all steps to the recipient, in relation to goods, being a standard that is prepared to deal withemergencies during transport and ensuring the safety of everyone .The study in question aims to obtain information about the exportprocess, highlighting its economic importance and the specificprocedures in the Brazilian market, which steps must be followed. The research will address the challenges involved in this process, in short, the detailed study of the steps and obstacles necessary in theexport of dangerous cargo.